Ultra-High Step-Up DC-DC Converters Based on Center-Tapped Inductors - Hadi Tarzamni; Naser Vosoughi Kurdkandi; Homayon Soltani Gohari; Matti Lehtonen; Oleksandr Husev; Frede Blaabjerg (IEEE Access, 2021)
In this paper, a new family of ultra-high step-up DC-DC converters based on a center-tapped coupled inductor (CI) is proposed. These single-switch converters employ different inductive and capacitive power transfer techniques by utilizing multi-winding CIs, intermediate capacitor links and simple switched-capacitors to improve the transferred power rate, harvest magnetizing and leakage inductance energies, and enhance power density. Achieving high voltage gain in low duty cycle values enables the proposed converters to operate under wide output voltage ranges; meanwhile, distributing the output voltage on two or three output ports alleviates the voltage stress on output terminal components. Low input current ripple, simple pulse width modulation control, low switch voltage stress and operation without circulating current can be listed as other features. In this paper, the proposed family is introduced, theoretically analyzed and compared with other state-of-the-art researches. Finally, the accuracy of analyses are evaluated with some experimental tests of a 1.25 kW experimental prototype.